THE RELATIONSHIP BETWEEN THE ROLE OF HEALTH WORKERS AND MOTIVATION FOR HIV/AIDS TESTING IN PREGNANT WOMEN - Purnani, Weni (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
HIV infection in pregnant women can harm both mother and child and more than 90% of cases of children with HIV are transmitted from mother to child. Motivation related to HIV testing in pregnant women is still very low, seen from when health workers offer HIV tests to all pregnant women who are visiting Antenatal Care. The purpose of this study is to determine the relationship between the role of health workers and the motivation for HIV/AIDS examination for pregnant women at the Campurejo Health Center, Mojoroto District, Kediri City in 2023. This type of research is quantitative using a crossectional design. By using the Simple Random Sampling sampling technique, the samples in this study were some pregnant women at the Campurejo Health Center, Mojoroto District, Kediri City amounting to 30 people. The data collection instrument in this study used a questionnaire sheet instrument. The research was conducted at the Campurejo Health Center, Mojoroto District, Kediri City. Bivariate analysis in this study used the spearman rho test. The results showed that almost half of the respondents who rated the role of health workers in the sufficient category were 14 respondents (46%), and some respondents had high motivation towards HIV/AIDS testing, namely 20 respondents (67%). The results of the statistical test of the correlation of Sperman Rho with a level of meaning p < 0.05 showed a relationship between the role of health workers and the motivation of pregnant women to be tested for HIV / AIDS at the Campurejo Health Center, Mojoroto District, Kediri City with p = 0.034 and r = 0.387. It is expected that health workers will always improve the quality of services providing counseling to clients, especially regarding HIV/AIDS examinations. Keywords: screening, HIV/AIDS, pregnant